Sosialisasi Alternatif Perbanyakan Tanaman Kakao pada Fase Pembibitan Menggunakan Metode Sambung Pucuk - Juang, Ignasius; Bolly, Yovita Yasintha; Jeksen, Julianus (LPPM Universitas Flores, 2023)
Superior seeds will guarantee good growth and high production levels if treatment is carried out optimally. To support plant development so that it is successful, the first step is to prepare planting material in the nursery. Efforts that can be made to support and increase cocoa production are through rejuvenating cocoa using the shoot grafting technique. Shoot grafting is often used by combining rootstock and scion. The rootstock is expected to be a stem that is resistant to soil pathogens and sturdy, while the scion is the part that has the desired production characteristics. Tools and materials used: grafting knife, plastic lid, raffia rope, sharpening stone, scion (scion). This activity was carried out in August-December 2023 in Bloro Village, Nita District, Sikka Regency using socialization and demonstration methods, interviews and literature reviews. prepare the rootstock from the seed nursery, the rootstock must have the following criteria: the plant grows healthily and is not attacked by pests and diseases, has strong roots, and the seed comes from a superior variety. The scion/tribe of the mother tree with the MCC 02 variety is productive, healthy and resistant to pest and disease attacks. Grafting is carried out on 3-month-old seedlings, by leaving 4-5 leaves, then the lower stem is split about 2 cm using a grafting knife so that both sides are the same. The entry is cut into a sharp or wedge shape and then inserted into the split rootstock. The entry that has been inserted is then tied with string, covered with ice plastic and tied again, when the shoots start to appear, the plastic is ready to be opened.